ETHICAL ASPECTS OF USING ARTIFICIAL INTELLIGENCE IN THE JUDICIARY: PARTH TO ENSURING HYMAN RIGHTS - PASCAR, AURICA (Ehrlich's Journal, 2023)
This article delves into the current issues surrounding the integration of artificial intelligence (AI) into the judiciary, with a focus on its advantages and ethical dilemmas. It contends that AI has the potential to enhance the accessibility and efficiency of justice by processing vast amounts of information and enhancing the impartiality of judicial decisions. The author emphasizes the necessity of formulating ethical standards and implementing oversight mechanisms for AI deployment in the judiciary to safeguard human rights and ensure judicial efficacy. Additionally, the article underscores AI’s capacity to streamline judicial processes and advocates for the establishment and enforcement of AI usage standards, alongside ongoing monitoring and algorithm refinement to uphold fairness and protect human rights. It underscores the crucial role of ethical principles in AI deployment and urges meticulous development and implementation of standards to uphold contemporary values’ stability. The analysis encompasses fundamental international and national regulatory sources governing AI’s ethical principles. In conclusion, the article asserts that given the contemporary challenges and possibilities of AI in the judiciary, ethical considerations become pivotal in its advancement. While AI can enhance judicial efficiency and fairness, conscientious attention to ethical dimensions and measures to oversee and safeguard human rights are imperative. Ensuring justice, transparency, accountability, security, and responsibility are vital prerequisites for AI integration. It is established that AI should align with ethical norms and values, rather than merely adhering to technical regulations. Successful AI integration in the judiciary necessitates collaboration among diverse stakeholders to formulate an ethical and legal framework that ensures the adequate protection of human rights in the era of artificial intelligence.